The Mesoscopic Constitutive Equations for Polymeric Fluids and Some Examples of Viscometric Flows - Pyshnograi, Gregory; Joda, Hyder N. A.; Pyshnograi, Ivan (My University, 2012)
Constitutive equations for melts and concentrated solutions of linear polymers are derived as consequences of dynamics of a separate macromolecule. The model is investigated for viscometric flows. It was shown that the model gives a good description of non-linear effects of simple shear polymer flows: viscosity anomalies, first and second normal stresses, non-steady shear stresses
Keywords: Rheology; Linear Polymer Melts and Solutions; Constitutive Equation; Mesoscopic Approach